An Exploration of Organisational Culture's Contribution to Job Stress in Cape Town Non-Profit Organisations, using the Culture-Work-Health Model - Kew, Ashleigh (Department of Social Development, 2021)
Organisational culture plays an essential role in the aetiology of job stress. Job stress has numerous negative effects including lower work performance and effectiveness, health problems and increased absenteeism. The direct and indirect costs associated with stress-related conditions, such as burnout, can result in reduced organisational commitment and engagement. Such situations require urgent attention from the management of any organisation, and it is essential that organisations take appropriate steps to avoid excessive stress of employees if they are to continue their vital work. The study uses the Culture-Work-Health Model as a framework to understand organisational culture and its contribution to job stress in Cape Town non-profit organisations (NPOs) working in the discipline of mental health and mental disability. An exploratory, qualitative research design was selected to develop an understanding of organisational culture in Cape Town NPOs. Seven employees from three NPOs, making up the total sample of 21 participants, were selected through non-probability, purposive sampling. From each organisation of seven employees, four were selected from management/leadership positions and three were selected from non-management in order to gain rich insightful data from both management and non-management perspectives. Data collection was done through semistructured, face-to-face interviews with the participants. The data was analysed through the use of Tesch's (1990) stages of analysis. Finally, a framework for analysis was developed based on the themes, categories and sub-categories that emerged. This study contributes to enhancing understanding of Cape Town NPO organisational culture, NPO management practices and job stress as well as providing a springboard for further research into these areas. A number of significant findings were made including: NPOs described a clan organisation-type culture with a committed and passionate staff; NPO management were perceived as unsupportive due to lack of transparency, which was exasperated by their inability to pay higher salaries; NPOs where management incorporate supervision and regular staff meetings were perceived more positively and reported fewer issues of miscommunication; and individuals who were able to incorporate a healthy work and non-work life balance thrived in the NPO setting. Based on these findings, a number of recommendations were made including: the development of an organisational mental health policy; mandatory regular staff meetings attended by all levels of staff to discuss general administrative issues; the communicated availability of support structures to staff, such as on-site counselling; and - very importantly - regular supervision for all staff members working directly with vulnerable clients.